Design and Implementation of Network Infrastructure at MTSS Salafiyah Al-Falah to Support Digital-Based Education Programs - Ibnu Asror; Sri Astuti; Ratna Mayasari; Yanuar Firdaus; Dawam Dwi Jatmiko Suwawi (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
Currently, in education, all reporting is mandated to be digital-based. Therefore, all reporting related to academic matters, school activities, and operations must use information systems. This community service activity is conducted at MTSS Salafiyah Al-Falah a madrasah type of school. Based on the initial survey conducted at the school, it was found that the school needs computer internetworking infrastructure support for the teaching and learning process as well as for school operational activities, such as recording school, student, and teacher data. MTSS Salafiyah Al-Falah must report monthly, and school exams also need a network infrastructure to ensure that online exams can run smoothly without issues. To address these problems, the community service team from Telkom University offered a solution to the school by designing and implementing the necessary network infrastructure. The network design and implementation results at MTSS Salafiyah Al-Falah provided ease in operational activities, a more stable internet network, and the successful execution of online exams without any issues.